The Linguistic Structure of Persuasive Discourse on Social Media (A Study in Persuasive Language Tools) - Ridwan Adewale Tidjani (Indonesian Journal of Arabic Studies, 2021)
This paper aims at studying the persuasion discourse on social networks, many of which are various and numerous, which made it impossible to contain easily, So this paper deliberately selected samples from these sites; and Twitter was selected as a case of study, because a single tweet is restricted to a number of alphabets. However, a tweeter will carefully work on selecting his words and utilize only the appropriate words that can convey his message. Therefore, the paper strictly focuses on the usages of language tools that a twitter uses to persuade a receiver with a message. And the Language strategies are one of the most prominent discourse strategies used by a sender regardless of the authenticity or non-authenticity of the content. So in order to achieve all these objectives, this paper focuses on collecting group of tweet that possesses or utilizes the language tools, and also characterized with a politely suitable content. However, the analysis of this discourse was basically a descriptive analysis, and its application has followed the process of selecting the tool, then expatiating the way the tools is utilized by analyzing how the discourse context of the tweet has achieved the persuasion. Finally This paper generally concluded that the persuasive discourse has a very dynamic structure, and that has made it more complicated to be narrowed in a very certain structure, in addition to that; senders tend to apply a more numeral and diversified methods that are renewable in accordance to the sender's style and language ability.Â ÙŠÙ‡Ø¯Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ ØªØÙ„ÙŠÙ„ Ø§Ù„Ø®Ø·Ø§Ø¨ Ø§Ù„Ø¥Ù‚Ù†Ø§Ø¹ÙŠ Ø¹Ù„Ù‰ Ù…ÙˆØ§Ù‚Ø¹ Ø§Ù„ØªÙˆØ§ØµÙ„ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØŒ ÙˆÙ„ÙƒØ«Ø±Ø© Ù‡Ø°Ù‡ Ø§Ù„Ù…ÙˆØ§Ù‚Ø¹ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ©ØŒ ÙˆØ¹Ø¯Ù… Ø¥Ù…ÙƒØ§Ù†ÙŠØ© Ø§Ù„Ø¥Ù„Ù…Ø§Ù… Ø¨Ø¬Ù…ÙŠØ¹Ù‡Ø§ØŒ ÙÙ‚Ø¯ ØªØ¹ÙŠÙ‘Ù† Ø¹Ù„Ù‰ Ø§Ù„Ø¨ØØ« Ø£Ù† ÙŠØªØ®ÙŠÙ‘Ø± Ù†Ù…Ø§Ø°Ø¬ ÙˆØ¹ÙŠÙ†Ø§Øª Ù…Ù† Ø¨Ø¹Ø¶Ù‡Ø§ØŒ ÙˆÙ„Ø°Ù„Ùƒ Ø§Ø®ØªÙŠØ± Ù…ÙˆÙ‚Ø¹ "ØªÙˆÙŠØªØ±"Ø› Ù„Ø£Ù† Ø§Ù„Ù…ØºØ±Ù‘Ø¯ Ù…Ù„Ø²Ù… ÙÙŠÙ‡ Ø¨Ø¹Ø¯Ø¯ Ù…ØØ¯Ø¯ Ù…Ù† Ø§Ù„ØØ±ÙˆÙØŒ ÙÙŠØ³Ø¹Ù‰ Ø¬Ø§Ù‡Ø¯Ø§ Ø¥Ù„Ù‰ ØªÙ‚Ù„ÙŠØµ Ø¹Ø¯Ø¯ ÙƒÙ„Ù…Ø§ØªÙ‡ØŒ ÙˆÙŠØªØ®ÙŠØ± Ù…Ù†Ù‡Ø§ Ù…Ø§ ÙŠØÙ‚Ù‚ Ø¨Ù‡ Ø§Ù„ØºØ±Ø¶ Ù…Ù† Ø§Ù„Ø±Ø³Ø§Ù„Ø©ØŒ Ù„Ø°Ø§ ÙƒØ§Ù† ØµÙ„Ø¨ Ø§Ù‡ØªÙ…Ø§Ù… Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø§Ù„Ø¹Ù†Ø§ÙŠØ© Ø¨Ø§Ù„Ø¢Ù„ÙŠØ§Øª Ø§Ù„Ù„ØºÙˆÙŠØ© Ø§Ù„ØªÙŠ ÙŠÙˆØ¸ÙÙ‡Ø§ Ø§Ù„Ù…ØºØ±Ù‘Ø¯ Ù„ØªÙˆÙ„ÙŠØ¯ Ø¥Ù‚Ù†Ø§Ø¹ Ø§Ù„Ù…Ø®Ø§Ø·Ø¨ Ø¨Ù…ØØªÙˆÙ‰ Ø®Ø·Ø§Ø¨Ù‡ØŒ ÙˆÙ‡ÙŠ Ù…Ù† Ø£Ù‡Ù… Ø§Ù„Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ§Øª Ø§Ù„ØªÙŠ ÙŠÙ‡Ø¯Ù Ø¥Ù„ÙŠÙ‡Ø§ Ø§Ù„Ù…Ø®Ø§Ø·Ø¨ Ø¨ØºØ¶ Ø§Ù„Ù†Ø¸Ø± Ø¹Ù† Ù…Ø¯Ù‰ ØµØØ© Ø§Ù„Ù…ØØªÙˆÙ‰ Ù…Ù† Ø¹Ø¯Ù…Ù‡Ø§ Ø£Ùˆ ØµØ¯Ù‚Ù‡Ø§ Ù…Ù† ÙƒØ°Ø¨Ù‡Ø§. ÙˆÙ„ØªØÙ‚ÙŠÙ‚ Ù‡Ø°Ø§ Ø§Ù„Ù‡Ø¯ÙØŒ Ø§ØªØ¬Ù‡ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ Ø¬Ù…Ø¹ Ù…Ø¬Ù…ÙˆØ¹Ø© Ù…Ù† Ø¹ÙŠÙ†Ø§Øª Ø§Ù„ØªØºØ±ÙŠØ¯Ø§ØªØŒ Ù…Ø¹ØªÙ…Ø¯Ø§ Ø¹Ù„Ù‰ Ø§Ù„ØªØºØ±ÙŠØ¯Ø§Øª Ø§Ù„ØªÙŠ ØªØªÙˆÙÙ‘Ø± ÙÙŠÙ‡Ø§ Ø§Ù„Ø¢Ù„ÙŠØ§Øª Ø§Ù„Ù„ØºÙˆÙŠØ© ÙˆÙˆÙØ¸Ù‘Ù ÙÙŠÙ‡Ø§ Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ§Øª Ù„ØºÙˆÙŠØ©ØŒ ÙˆØªÙƒÙˆÙ† -ÙÙŠ Ø§Ù„ÙˆÙ‚Øª Ù†ÙØ³Ù‡- Ù…Ù„Ø§Ø¦Ù…Ø© Ù„Ù„Ø¢Ø¯Ø§Ø¨ Ø§Ù„Ø¹Ø§Ù…Ø© Ù…Ù† ØÙŠØ« Ù…ØØªÙˆØ§Ù‡Ø§ØŒ Ø¨Ø¹ÙŠØ¯Ø© Ø¹Ù† Ø§Ù„ØªØ¹Ø¨ÙŠØ±Ø§Øª Ø§Ù„Ø³Ø§Ù‚Ø·Ø©. Ø£Ù…Ø§ ØªØÙ„ÙŠÙ„ Ù‡Ø°Ù‡ Ø§Ù„Ø®Ø·Ø§Ø¨Ø§Øª ÙÙ‚Ø¯ ÙƒØ§Ù†Øª Ø°Ø§Øª Ø³Ù…Ø© ÙˆØµÙÙŠØ©ØŒ Ø¨ØÙŠØ« ÙŠØ¹Ù…Ø¯ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ ØªØØ¯ÙŠØ¯ Ø§Ù„Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø§Ù„Ù„ØºÙˆÙŠØ© ÙÙŠ Ø§Ù„Ø®Ø·Ø§Ø¨ØŒ Ø«Ù… ÙŠØ¨ÙŠÙ† ÙƒÙŠÙÙŠØ© ØªÙˆØ¸ÙŠÙÙ‡Ø§ Ù…Ù† Ø®Ù„Ø§Ù„ ØªØÙ„ÙŠÙ„ Ø³ÙŠØ§Ù‚ Ø§Ù„Ø®Ø·Ø§Ø¨ Ø§Ù„ØªÙŠ ÙˆØ¸ÙÙ‡Ø§ ÙÙŠÙ‡Ø§ Ø§Ù„Ù…ØºØ±Ù‘Ø¯ Ù„ØªÙˆÙ„ÙŠØ¯ Ø§Ù„Ø¥Ù‚Ù†Ø§Ø¹. ÙˆÙ‚Ø¯ Ø®Ù„Øµ Ø§Ù„Ø¨ØØ« ÙÙŠ Ø£Ø¨Ø±Ø² Ù†ØªØ§Ø¦Ø¬Ù‡ Ø§Ù„Ø¹Ø§Ù…Ø© Ø¥Ù„Ù‰ Ø£Ù† Ø§Ù„Ø®Ø·Ø§Ø¨ Ø§Ù„Ø¥Ù‚Ù†Ø§Ø¹ÙŠ Ø®Ø·Ø§Ø¨ Ø¯ÙŠÙ†Ø§Ù…ÙŠÙƒÙŠ Ù…Ù† Ø§Ù„Ø·Ø±Ø§Ø² Ø§Ù„Ø£ÙˆÙ„ØŒ Ø¥Ø° Ø¥Ù† Ø§Ù„Ù…Ø±Ø³Ù„ ÙƒØ«ÙŠØ±Ø§ Ù…Ø§ ÙŠØªÙˆØ¬Ù‡ Ø¥Ù„Ù‰ ØªÙˆÙ„ÙŠØ¯ Ø¢Ù„ÙŠØ§Øª Ù…ØªØ¹Ø¯Ø¯Ø© ÙˆØ§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ§Øª Ù…Ø®ØªÙ„ÙØ©ØŒ ÙŠØ®ØªØ§Ø±Ù‡Ø§ ØªÙ„Ù‚Ø§Ø¦ÙŠØ§ Ø·Ø§Ù„Ù…Ø§ Ø£Ù† Ù„Ø¯ÙŠÙ‡ Ù‚Ù†Ø§Ø¹Ø§Øª Ø¨Ù‚Ø¯Ø±Ø© Ù‡Ø°Ù‡ Ø§Ù„Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø¹Ù„Ù‰ Ø§Ù„ØªØ£Ø«ÙŠØ± ÙÙŠ Ø§Ù„Ù…ØªÙ„Ù‚ÙŠØŒ Ø¨Ù†Ø§Ø¡ Ø¹Ù„Ù‰ Ø°Ù„Ùƒ ÙŠØªÙˆØ¬Ù‡ -ØºØ§Ù„Ø¨Ø§- Ø¥Ù„Ù‰ ØªÙˆØ¸ÙŠÙ ÙƒØ«ÙŠØ± Ù…Ù† Ø§Ù„Ø¢Ù„ÙŠØ§Øª Ø§Ù„Ù„ØºÙˆÙŠØ© Ø§Ù„ØªÙŠ ØªØªØ¬Ø¯Ø¯ Ù…Ø¹Ù‡Ø§ Ø§Ù„Ø¨Ù†ÙŠØ© Ø§Ù„Ù„ØºÙˆÙŠØ© Ù„Ù„Ø®Ø·Ø§Ø¨ Ø¹Ù„Ù‰ ØØ³Ø¨ Ø£Ø³Ù„ÙˆØ¨Ù‡ ÙˆÙ…Ù‚Ø¯Ø±ØªÙ‡ Ø§Ù„Ù„ØºÙˆÙŠØ©.